PENGARUH PERBEDAAN SUMBER PUPUK NITROGEN DAN JENIS AMELIORAN TERHADAP PERTUMBUHAN DAN HASIL SERTA SERAPAN NITROGEN TANAMAN PAKCOY (Brassica rapa L.) MELALUI FERTIGASI SISTEM SUMBU DALAM VERTIKULTUR DI LAHAN KERING - YOVITA NONI OPAT; Opat, Yovita Noni; Tobing, Wilda Lumban; Tefa, Azor Yulianus; Ndua, Natalia Desy Djata (University of Prof. Dr. Hazairin, SH, 2024)
Pakcoy (Brassica rapa L.) is a green vegetable plant that is in great demand by people from children to adults, because it has very high nutritional value. Cultivation of pak choy plants on dry land with a dry climate requires the adoption of technology such as wick fertigation in verticulture. The aim of this research was to determine the effect of providing nitrogen fertilizer sources and types of ameliorant on the growth and yield as well as nitrogen uptake of pak choy (Brassicca rapa L.) plants. This research method uses a split plot design (RPT) with 2 factors consisting of a main plot and a subplot. The main plot is N fertilizer consisting of urea, POC, and urea + POC. Subplots are ameliorants consisting of soil, soil: biochar (1:1), soil: compost (1:1) and soil: biochar: compost (1:1:1). Thus, 12 treatment combinations were obtained which were repeated 3 times, resulting in a total of 36 experimental combinations. The research results showed that the interaction of the N fertilizer source and the type of ameliorant had a real influence on the observation of stem diameter and root length with the best treatment of urea+POC with the type of soil ameliorant: biocar: compost (1:1:1). The source of N fertilizer has a significant effect on shoot dry weight, harvest index and N uptake, where the best treatment is urea+POC fertilizer. The type of ameliorant had a significant effect on the number of leaves at 28 DAT and N content where the best treatment was soil: biochar: compost (1:1:1) showing the highest results when observing the number of leaves at 28 DAP and N content. Treatment of the type of soil ameliorant: biochar: compost (1:1:1) shows the best results.